Tipologi penggunaan dan perubahan lahan berbasis spasial: pendekatan studi kasus di kabupaten jayapura - Donie T. Watopa; Antoni Ungirwalu; Soetjipto Moeldjono; Jimmy F. Wanma; Petrus A. Dimara (Cassowary, 2022)
Jayapura Regency is an area in Papua Province with relatively rapid growth since it was formed into a district in 2016. Over the last ten years, massive land use and changes have occurred in Jayapura Regency. Changes in land use can be identified by looking at the land use that occurred in the past and present. Land use change is an unavoidable process, so it is important to study it empirically and in multi-time observations for development planning. In this regard, the formulation of the problem is that the types of land use and change in Jayapura Regency are not yet known with a case study of the spatial approach in 2005 and 2018. Based on the formulation of the problem, the purpose of this study is to determine the typology of land use and change in Jayapura Regency for 2005 and 2018. It is hoped that this study will become a data base and spatial information on land use in Jayapura Regency and enrich knowledge about spatial models of land use change that can be used as an approach to regional development planning. The results of the study show that based on land use classification in Jayapura Regency, there are 20 typologies of land use where primary dry land forest type has an area of ​​983,713.71 ha or 67.98% of the total area. Most of these forests are state forest areas with protection and production functions. During the period 2005 – 2018, Jayapura Regency lost 6,508.08 ha of forested area with an average rate of forest depreciation reaching more than 500.62 ha annually, while open land changed functions almost half of its original use.